The Influence of Taxpayer Awareness and Tax Sanctions on Individual Taxpayer Compliance - Devira Indrasvari Naryana, Putu; Setiawan, Putu Ery (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
Taxes represent the largest contribution to state revenue, but taxpayer compliance in fulfilling their obligations is still not optimal. Taxpayer awareness and the imposition of tax sanctions can influence taxpayer compliance in fulfilling their tax obligations. This study aims to obtain empirical evidence of the effect of taxpayer awareness and tax sanctions on taxpayer compliance. The population in this study is individual taxpayers registered at KPP Pratama Badung Utara. The sample used consists of 100 individual taxpayers selected through non-probability sampling, specifically purposive sampling, with data analysis using multiple linear regression. The results of this study indicate that taxpayer awareness and tax sanctions have a positive effect on taxpayer compliance at KPP Pratama Badung Utara.